LISENSI BAGI PEMANDU WISATA DALAM MENJALANKAN PROFESI KEPARIWISATAAN DI KABUPATEN BADUNG - Arif Sanjaya, Putu; Dewi Kasih, Desak Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
The development of tourism in Bali is growing rapidly so do not rule gave rise to an unlicensed tour guide or often called guide illegal, as the license is a license that grants the right to organize a company. Licenses are used to express permission allows a separately run a company with a special permit or special. Each guide is required to have a license in order to support tourism in the area, but there are guides Badung particularly guide illegal that do not have a license to harm the tourism industry, therefore, this article will explain the importance of licenses for tour guides and the advancement of the tourism industry in the area of Badung. In addition, this paper also explains the role of the government in dealing with illegal guide in Badung district. to get the most out of writing the research method used is empirical legal research techniques of data collection through interviews with informants. The function is as a guide license for legal protection for tour guides in their profession, while the actions of the Bali provincial government in dealing with the guides without permission is sweeping / raids against guides at tourist spots and supervision to unlicensed guides are caught.
Keywords: tourism, licensed tour guides, guide ilegal